ChemInform Abstract: Copper‐Catalyzed Tandem Reactions of 2‐Iodobenzamides with Sodium Azide: An Efficient Synthesis of [1, 2, 3]Triazolo[1, 5‐a][1, 4]‐benzodiazepin‐6(5H)‐ones. Issue 33 (August 2015) - Chen, Wanli; Li, Haitao; Gu, Xiaoling; Zhu, Yinghong
Abstract The title compounds are efficiently obtained by reaction of 2‐iodobenzamides with a propargyl group on the nitrogen atom moiety and sodium azide under mild reaction conditions.